Coupled-ridge waveguide quantum cascade laser array lasing at λ 5 µm. (September 2021) - Yang, Pengchang; Zhang, Jinchuan; Gu, Zenghui; Liu, Chuanwei; Zhao, Yue; Cheng, Fengmin; Zhai, Shenqiang; Zhuo, Ning; Liu, Junqi; Wang, Lijun; Liu, Shuman; Liu, Fengqi
Abstract: In this work, we demonstrated high-power quantum cascade laser (QCL) arrays lasing at λ 5 µ m by employing an optimized coupled-ridge waveguide (CRW) structure. Five-element QCL arrays were simulated and fabricated through a two-step etching method to extend the CRW structure to a mid-wave infrared regime. A lateral far-field with the main peak near a diffraction-limited intensity curve of about 10° was observed by properly designing a geometric shape of the ridges and interspaces. By introducing a buried 2nd-order distributed feedback (DFB) grating, substrate emission with a radiation power above 1 W at 25 °C is achieved. Single longitudinal mode operation is obtained by changing the temperature of the heatsink with a good linear wavelength tuning coefficient of –0.2 cm –1 /K.